2008
DOI: 10.1093/jn/138.6.1053
|View full text |Cite
|
Sign up to set email alerts
|

Cats Are Able to Adapt Protein Oxidation to Protein Intake Provided Their Requirement for Dietary Protein Is Met

Abstract: Cats require more dietary protein than noncarnivorous species. Earlier work showed that cats lack the ability to regulate hepatic urea cycle enzymes in response to dietary protein concentration. We thus hypothesized that cats are unable to fully adapt protein oxidation to protein intake, particularly at low-protein concentrations. We used indirect respiration calorimetry to assess cats' ability to adapt substrate oxidation to diets containing different concentrations of protein, including 1 below their protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 42 publications
2
51
5
Order By: Relevance
“…Russell et al, 2002;Green et al, 2008). Our findings in another strict carnivore, the mink, indicate that foetal life protein malnutrition leads to a lower protein oxidation, calculated as a percentage of total heat production.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Russell et al, 2002;Green et al, 2008). Our findings in another strict carnivore, the mink, indicate that foetal life protein malnutrition leads to a lower protein oxidation, calculated as a percentage of total heat production.…”
Section: Discussionmentioning
confidence: 57%
“…Both in vitro (Kettelhut et al, 1980;Silva and Mercer, 1985) and in vivo studies (Russell et al, 2000) have shown that cats have some ability to adapt to dietary protein provision in terms of changes in ureagenesis and gluconeogenesis. Further, Russell et al (2002) found that protein oxidation was correlated to some extent to dietary protein intake in cats, but only if the protein requirement was met (Green et al, 2008). Studies in mink have, however, shown that the rates of amino acid decarboxylation (Tauson et al, 2001) and protein oxidation are regulated according to the dietary protein supply, even if the level of dietary protein is low (Fink et al, 2004) or below the requirement (Matthiesen et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on the protein requirements of cats has established the capacity of cats for handling large protein loads and their failure to sufficiently reduce catabolism when faced with low-protein diets (Rogers et al 1977;Russell et al 2000Russell et al , 2002Russell et al , 2003Rogers and Morris 2002;Russell 2002;Green et al 2008). In this paper, I propose a mechanistic explanation for why cats are unable to downregulate catabolic enzymes, and thus amino acid oxidation, to the same degree as non-hypercarnivorous mammals.…”
Section: Introductionmentioning
confidence: 95%
“…This is particularly remarkable since most cats used in scientific studies are maintained on diets (Miller and Allison 1958;Greaves and Scott 1960;Biourge et al 1994;Hendriks et al 1997;Russell et al 2000Russell et al , 2002Russell et al , 2003Green et al 2008) that contribute 5-20 times the amount of carbohydrate on a ME basis than what might be considered the 'natural' diet of the species (Table 2). In other words, high rates of gluconeogenesis in the cat appear to be essentially preserved despite a significant intake of carbohydrate.…”
Section: Gluconeogenesismentioning
confidence: 99%
See 1 more Smart Citation